RESEARCH AND DEVELOPMENT OF A NEW METHOD OF WASTE DISPOSAL FOR ISOLATED SITES IN THE ARCTIC. 1, FUNDAMENTALS OF HUMAN WASTE INCINERATION. - Miholits,Ernest M. (1961)
In cooperation with Northwestern Univ., Evanston, Ill.